The Effects of Female Board of Director, Female Audit Committee, and CEO Power on Carbon Emission Disclosure - Kristianing Yesa; Syaiful Iqbal (Department of Accounting, Faculty of Economics & Business, 2026)
Carbon emission disclosure in Indonesia remains voluntary, leading to substantial variation in reporting practices across firms. This study examines the effects of female board members, the presence of female audit committee members, and CEO power on carbon emission disclosure among companies listed in the IDX LQ45 Low Carbon Leaders index during 2022–2023. Using purposive sampling and multiple linear regression, the study finds that female board representation has no significant effect on carbon emission disclosure, whereas female audit committees and CEO power positively affect it. Management ownership, as a control variable, shows a significant negative effect. This study offers novel evidence by differentiating the effectiveness of gender diversity across governance layers and jointly examining executive ownership power within a low-carbon index in an emerging market context. The results provide relevant implications for sustainability-oriented governance design and investment evaluation.